Chameleons in the early universe: kicks, rebounds, and particle production - Erickcek, Adrienne L.; Barnaby, Neil; Burrage, Clare; Huang, Zhiqi (American Physical Society, 2014)
Chameleon gravity is a scalar-tensor theory that includes a nonminimal coupling between the scalar field and the matter fields and yet mimics general relativity in the Solar System. The scalar degree of freedom is hidden in high-density environments because the effective mass of the chameleon scalar depends on the trace of the stress-energy tensor. In the early Universe, when the trace of the matter stress-energy tensor is nearly zero, the chameleon is very light, and Hubble friction prevents it from reaching the minimum of its effective potential. Whenever a particle species becomes nonrelativistic, however, the trace of the stress-energy tensor is temporarily nonzero, and the chameleon begins to roll. We show that these “kicks” to the chameleon field have catastrophic consequences for chameleon gravity. The velocity imparted to the chameleon by the kick is sufficiently large that the chameleon’s mass changes rapidly as it slides past its potential minimum. This nonadiabatic evolution shatters the chameleon field by generating extremely high-energy perturbations through quantum particle production. If the chameleon’s coupling to matter is slightly stronger than gravitational, the excited modes have trans-Planckian momenta. The production of modes with momenta exceeding 107 GeV can only be avoided for small couplings and finely tuned initial conditions. These quantum effects also significantly alter the background evolution of the chameleon field, and we develop new analytic and numerical techniques to treat quantum particle production in the regime of strong dissipation. This analysis demonstrates that chameleon gravity cannot be treated as a classical field theory at the time of big bang nucleosynthesis and casts doubt on chameleon gravity’s viability as an alternative to general relativity.